Membrane electrode for anion exchange membrane water electrolysis hydrogen production and preparation method thereof

By adopting direct coating technology on the anion exchange membrane to form a membrane electrode with low impedance and high catalytic activity, the existing membrane electrodes of the existing membrane electrode in the electrolyte hydrogenation process, high impedance and high expansion rates , Realize efficient electrolytic water hydrogen.

CN119332269AActive Publication Date: 2025-01-21XIAMEN UNIV

Patent Information

Application Number
CN202411384493.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-30
Publication Date
2025-01-21
Estimated Expiration
2044-09-30

AI Technical Summary

Technical Problem

During the electrolytic hydrogen production process of existing membrane electrodes, catalytic layer falls off, reduced effective active area, high impedance, high swelling rate and complex preparation process, which is difficult to meet the needs of large-scale applications.

Method used

The two sides of the anion exchange film are used to coat the catalyst and the anode catalyst slurry, respectively, and control the coating temperature of 40 ° C to 100 ° C through gradient and appropriate coating speed to form low impedance and catalytic activity. High membrane electrode.

Benefits of technology

The impedance of the membrane electrode is reduced, the catalytic activity is improved, the swelling rate is controlled at a low level, the catalytic layer is firmly combined with the anion exchange membrane, the preparation process is simplified, and the efficiency of hydrogen production by electrolysis of water is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119332269A_ABST
    Figure CN119332269A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of water electrolysis hydrogen production devices, in particular to a membrane electrode for water electrolysis hydrogen production of an anion exchange membrane and a preparation method of the membrane electrode. The membrane electrode comprises an anion exchange membrane with two side surfaces, wherein a cathode catalyst layer is arranged on the first side surface of the anion exchange membrane; and / or an anode catalyst layer is arranged on the second side surface of the anion exchange membrane; the cathode catalyst layer and the anode catalyst layer are solid catalyst layers formed by coating two side surfaces of the anion exchange membrane with cathode catalyst slurry and anode catalyst slurry and curing the cathode catalyst slurry and the anode catalyst slurry respectively; the cathode catalyst slurry and the anode catalyst slurry are designed according to a specific formula. The membrane electrode has the advantages of low impedance, high catalytic activity, low swelling rate or no swelling rate, firm combination of a catalytic layer and an anion exchange membrane, simple preparation process flow and the like, is applied to an AEM electrolytic cell, and does not cause the defects of volume expansion of an electrolytic cell stack, poor sealing performance, falling of the catalytic layer and the like in the process of assembling the electrolytic cell stack; and the water electrolysis hydrogen production efficiency can be obviously improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of water electrolysis hydrogen production devices, and in particular to a membrane electrode for anion exchange membrane water electrolysis hydrogen production and a preparation method thereof. Background Art

[0002] After decades of development, a variety of viable water electrolysis technologies have emerged, including alkaline water electrolysis (ALK), proton exchange membrane (PEM), anion exchange membrane (AEM), and solid oxide electrolysis (SOEC). AEM electrolysis, combining the low cost of ALK with the high efficiency and convenience of PEM, has become the latest development in water electrolysis hydrogen production.

[0003] The AEM electrolyzer, a device that converts electrical energy into chemical energy, is the core component of the AEM water electrolysis hydrogen production system. The AEM electrolyzer primarily consists of end plates, bipolar plates, a gas diffusion layer, an AEM, and a membrane electrode. The membrane electrode is the primary reaction site in the entire water electrolysis hydrogen production system and consists of an anode catalyst, a cathode catalyst, and the AEM.

[0004] Membrane electrodes are primarily fabricated using the catalyst-coated diffusion layer (CCS) method and the catalyst-coated membrane (CCM) method. The difference between the two methods lies in the location of the catalyst layer: in the CCS method, the catalyst slurry is adhered to the surface of the gas diffusion layer, while in the CCM method, the catalyst slurry is attached to the ion exchange membrane. Due to swelling issues with AEM membranes, there are few reports on using the CCM method for membrane electrodes on AEM membranes. The CCM method is generally used for proton exchange membranes.

[0005] The CCS method is obtained by spraying or coating the active components of the catalyst directly on the diffusion layer. On the one hand, the catalytic layer is in an exposed state. As the electrolysis of water to produce hydrogen proceeds, the catalytic layer is easy to fall off, and the catalyst particles in the catalytic layer will gradually agglomerate, causing the effective active area of ​​the catalytic layer to continue to decrease and the catalytic ability to gradually decrease. On the other hand, the stratification between the catalytic layer and the anion exchange membrane makes the membrane electrode have a higher impedance, affecting the efficiency of hydrogen production by electrolysis of water. The spraying process operating parameters are relatively simple to control, the equipment cost is low, and a wider range of slurry viscosities can be accepted, but its disadvantages are that there is a lot of material waste, low production capacity, and it cannot meet large-scale applications.

[0006] The CCM method reduces the contact distance between the catalyst layer and the anion exchange membrane, eliminating the contact gap between the catalyst layer and the anion exchange membrane and reducing ion conduction resistance. However, the preparation process is generally complex and can easily cause the anion exchange membrane to swell, thereby disrupting the morphology and structure of the prepared catalyst layer, causing cracks, peeling, or even complete detachment of the catalyst layer. This can also lead to volume expansion, poor sealing, and poor electrochemical performance during electrolyzer stack assembly. Summary of the Invention

[0007] To address the deficiencies of the prior art mentioned in the above background technology, the present application provides a membrane electrode for hydrogen production by water electrolysis using an anion exchange membrane. The membrane electrode has the advantages of low impedance, high catalytic activity, low or no swelling rate, strong bonding between the catalytic layer and the anion exchange membrane, and a simple preparation process. Its use in an AEM electrolyzer can significantly improve the efficiency of hydrogen production by water electrolysis. The specific technical solution is as follows: The present application provides a membrane electrode for hydrogen production by water electrolysis using an anion exchange membrane, which includes an anion exchange membrane having two sides; a cathode catalyst layer is provided on the first side of the anion exchange membrane; and / or an anode catalyst layer is provided on the second side of the anion exchange membrane; wherein the cathode catalyst layer is a solid catalyst layer formed by coating a cathode catalyst slurry on the first side of the anion exchange membrane and curing; the anode catalyst layer is a solid catalyst layer formed by coating an anode catalyst slurry on the second side of the anion exchange membrane and curing; the components of the cathode catalyst slurry include, by mass fraction, 15% to 20% of a cathode catalyst, 35% to 40% of water, 35% to 40% of an alcohol organic solvent, and 5% to 10% of an ionomer solution; the components of the anode catalyst slurry include, by mass fraction, 15% to 20% of an anode catalyst, 35% to 40% of water, 35% to 40% of an alcohol organic solvent, and 5% to 10% of an ionomer solution.

[0008] In some embodiments, the components of the cathode catalyst slurry consist of a cathode catalyst, water, an alcohol organic solvent, and an ionomer solution, and the cathode catalyst slurry is obtained by stirring and mixing the cathode catalyst, water, an alcohol organic solvent, and an ionomer solution for 3 to 5 hours; the components of the anode catalyst slurry consist of an anode catalyst, water, an alcohol organic solvent, and an ionomer solution, and the anode catalyst slurry is obtained by stirring and mixing the anode catalyst, water, an alcohol organic solvent, and an ionomer solution for 3 to 5 hours.

[0009] In some embodiments, during the coating process of the cathode catalyst slurry and the anode catalyst slurry, the coating is performed by gradient controlling the coating temperature of 40°C to 100°C, and the coating speed is 0.2 to 0.5 m / min; the process of gradient controlling the coating temperature of 40°C to 100°C is as follows: the coating temperature is first raised from room temperature to 40 to 50°C, and after the coating is completed, the temperature is continued to be raised to 60°C and maintained at a constant temperature for 15 minutes, and then the temperature is raised to 80 to 100°C, and the constant temperature of 80 to 100°C is maintained until the formed cathode catalyst layer or the anode catalyst layer is completely dry, and the heating is stopped.

[0010] In some embodiments, the ionomer in the ionomer solution is a polybiphenyl alkylene polymer ionomer, so that the cathode catalyst layer or the anode catalyst layer forms a strong electrode structure; the carrier of the cathode catalyst is a porous carbon nanomaterial; and the alcohol organic solvent is isopropyl alcohol.

[0011] In some embodiments, the anion exchange membrane has a thickness of 20 to 160 μm.

[0012] In some embodiments, the thickness of the cathode catalyst layer and the anode catalyst layer are both 0.1 to 20 μm.

[0013] In some embodiments, the total thickness of the membrane electrode is 0.02 to 0.2 mm.

[0014] The present application also provides a method for preparing a membrane electrode for producing hydrogen by electrolysis of water using an anion exchange membrane, which comprises the following steps: Cutting the anion exchange membrane into the required size; Coating a cathode catalyst slurry and an anode catalyst slurry on two opposite sides of the anion exchange membrane, drying and curing the slurry to form a cathode catalyst layer and an anode catalyst layer on the two sides of the anion exchange membrane; Among them, the components of the cathode catalyst slurry include, by mass fraction: 15% to 20% of cathode catalyst, 35% to 40% of water, 35% to 40% of alcohol organic solvent, and 5% to 10% of ionomer solution; the components of the anode catalyst slurry include, by mass fraction: 15% to 20% of anode catalyst, 35% to 40% of water, 35% to 40% of alcohol organic solvent, and 5% to 10% of ionomer solution.

[0015] In some embodiments, during the coating of the cathode catalyst slurry and the anode catalyst slurry, a gradient-controlled coating temperature of 40°C to 100°C is used for coating, and a coating speed is 0.2 to 0.5 m / min; wherein, the process of gradient-controlled coating temperature of 40°C to 100°C is as follows: the coating temperature is first raised from room temperature to 40 to 50°C, and after coating is completed, the temperature is continued to be raised to 60°C and maintained at a constant temperature for 15 minutes, and then the temperature is raised to 80 to 100°C, and the constant temperature of 80 to 100°C is maintained until the formed cathode catalyst layer or the anode catalyst layer is completely dry, and heating is stopped.

[0016] In some embodiments, the preparation method comprises the following steps: Cutting the anion exchange membrane to the required size, and then placing the anion exchange membrane flat on the substrate; wherein the anion exchange membrane is sealed with tape on all sides and vacuum adsorption is maintained to ensure that the anion exchange membrane is flat; Cathode catalyst slurry and anode catalyst slurry are coated on two opposite sides of the anion exchange membrane respectively, dried and solidified to form cathode catalyst layer and anode catalyst layer, and then the tape around the anion exchange membrane is removed and the membrane is packaged for storage.

[0017] Based on the above, compared with the existing technology, the present application solution has the following beneficial effects: The membrane electrode for hydrogen production by anion exchange membrane electrolysis provided herein has the advantages of low impedance, high catalytic activity, low or no swelling rate, strong bonding between the catalytic layer and the anion exchange membrane, and a simple preparation process. Its application in AEM electrolyzers prevents defects such as cell stack volume expansion and poor sealing during assembly, and significantly improves the efficiency of hydrogen production by water electrolysis.

[0018] Other features and benefits of the present application will be described in the following description, and in part will become apparent from the description or be understood by practicing the present application. The objectives and other benefits of the present application can be achieved and obtained through the structures particularly pointed out in the description, claims, and drawings. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] To make the purpose, technical solutions, and advantages of the embodiments of the present application more clear, the technical solutions in the embodiments of the present application will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without making creative efforts are within the scope of protection of this application.

[0020] Figure 1 This is a surface microscope image of the membrane electrode prepared in Example 1 of the present application; Figure 2 This is a scanning electron microscope image of a cross section of the membrane electrode prepared in Example 1 of the present application; Figure 3 This is a surface scanning electron microscope image of the membrane electrode prepared in Example 1 of the present application; Figure 4 This is an impedance spectrum (EIS) diagram of the membrane electrode prepared in Example 1 of the present application; Figure 5 This is a polarization curve diagram of the membrane electrode prepared in Example 1 of the present application; Figure 6 This is a physical display of the membrane electrode product prepared in Example 1 of the present application. DETAILED DESCRIPTION

[0021] In order to make the purpose, technical solutions and advantages of the embodiments of the present application clearer, the technical solutions in the embodiments of the present application will be clearly and completely described below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are part of the embodiments of the present application, not all of the embodiments; the technical features designed in different implementation modes of the present application described below can be combined with each other as long as they do not conflict with each other; based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of this application.

[0022] In the description of this application, it should be noted that all terms used in this application (including technical terms and scientific terms) have the same meanings as those commonly understood by ordinary technicians in the field to which this application belongs, and should not be understood as limiting this application; it should be further understood that the terms used in this application should be understood to have meanings consistent with the meanings of these terms in the context of this specification and the relevant field, and should not be understood in an idealized or overly formal sense, unless explicitly defined as such in this application.

[0023] An example of a method for preparing a membrane electrode for producing hydrogen by electrolysis of water using an anion exchange membrane is provided in this application as follows: The preparation process of the membrane electrode for anion exchange membrane water electrolysis to produce hydrogen provided by the present application comprises the following steps: Step 1: Cut the anion exchange membrane to the required dimensions and then lay it flat on the substrate. The membrane is sealed with tape on all sides and vacuumed to ensure it remains flat. This ensures the membrane's flatness and prevents the formation of microscopic holes in the membrane caused by vacuum extraction.

[0024] Among them, the surface flatness of the anion exchange membrane will affect the adhesion of the coating and the final membrane electrode flatness. Therefore, maintaining the flatness of the anion exchange membrane during this process is beneficial to improving the quality of the membrane electrode.

[0025] Step 2: Coat the cathode catalyst slurry and the anode catalyst slurry on two opposite sides of the anion exchange membrane, dry and solidify them to form a cathode catalyst layer and an anode catalyst layer, then remove the tape around the anion exchange membrane and package it for storage.

[0026] The membrane electrode prepared by the above preparation method has the following structure: it comprises an anion exchange membrane with two sides; the first side and the second side of the anion exchange membrane are provided with an anode catalyst layer and a cathode catalyst layer respectively.

[0027] It should be noted that: according to process requirements, it is also possible to choose to coat only one side of the membrane electrode, that is, only coat to form the anode catalyst layer or the cathode catalyst layer.

[0028] For the slurry formula setting and process parameter setting in the preparation process of the membrane electrode: (1) The slurry formula is: Cathode catalyst slurry: The components of the cathode catalyst slurry are composed of cathode catalyst, water, alcohol organic solvent, and ionomer solution. Calculated by mass fraction, the components of the cathode catalyst slurry include: 15% to 20% cathode catalyst, 35% to 40% water, 35% to 40% alcohol organic solvent, and 5% to 10% ionomer solution; the cathode catalyst slurry is obtained by stirring and mixing the cathode catalyst, water, alcohol organic solvent, and ionomer solution for 3 to 5 hours.

[0029] Anode catalyst slurry: The anode catalyst slurry consists of an anode catalyst, water, an alcoholic organic solvent, and an ionomer solution. By mass, the anode catalyst slurry comprises: 15% to 20% anode catalyst, 35% to 40% water, 35% to 40% alcoholic organic solvent, and 5% to 10% ionomer solution. The anode catalyst slurry is prepared by stirring and mixing the anode catalyst, water, alcoholic organic solvent, and ionomer solution for 3 to 5 hours.

[0030] Alternatively, the ionomer in the ionomer solution is a polybiphenyl alkylene polymer ionomer, the cathode catalyst carrier is a porous carbon nanomaterial, and the alcohol organic solvent is isopropyl alcohol.

[0031] (2) Coating process control is: During the coating process of the cathode catalyst slurry and the anode catalyst slurry, a coating temperature of 40°C to 100°C is gradient-controlled, and the coating speed is 0.2 to 0.5 m / min. The specific process of gradient-controlled coating temperature of 40°C to 100°C is as follows: the coating temperature is first raised from room temperature to 40 to 50°C. After coating is completed, the temperature is further raised to 60°C and maintained at this temperature for 15 minutes. The temperature is then raised to 80 to 100°C and maintained at this temperature until the formed cathode catalyst layer or the formed anode catalyst layer is completely dry, at which time heating is stopped.

[0032] This application adopts the above-mentioned preparation process and controls the above-mentioned slurry to adopt the above-mentioned specific formula and coating process parameters to achieve the desired effect. Its design concept and working principle are: The direct coating technology used in this application directly coats the catalyst slurry onto the ion exchange membrane, and the membrane is prone to swelling when it encounters solvents. Therefore, the parameters and formula control of the direct coating technology process are very critical.

[0033] In the slurry, ionomers primarily serve to conduct ions and also act as a catalyst binder. Therefore, the ionomer content in the catalyst layer needs to be controlled within a reasonable ratio. Controlling the ionomer content within a certain mass ratio in the slurry can achieve the desired effect of this application. If the ionomer content is too low (below the specified range of this application), the number of three-phase interfaces is insufficient, and the ions cannot fully contact the catalyst, thus failing to effectively function as a catalyst. However, if the ionomer content is too high (above the specified range of this application), the porosity of the catalyst layer decreases, leading to blockage of gas channels in the catalyst layer, thereby hindering gas transmission and water removal. Concentration polarization increases, affecting electrolysis efficiency.

[0034] The carrier in the catalyst is a porous carbon nanomaterial. Due to its high specific surface area, the porous carbon nanomaterial is prone to agglomeration during the slurry mixing and dispersion process. The slurry is a non-Newtonian fluid, dispersed in the solvent in the form of small solid particles. These small solid particles have both adsorption and repulsion effects on each other. When the adsorption force is greater than the repulsion force, the particles are attracted to each other, and the powder particles are prone to agglomeration, which affects the subsequent coating operation. Therefore, if the slurry formula is not designed properly, the slurry will settle during storage. The solid matter such as the catalyst is controlled within a certain mass ratio range (that is, the solid matter such as the catalyst is controlled within a certain range to limit the solid content of the slurry within a certain range. This article uses solid content to characterize the stability of the slurry). This ensures that the catalyst content is sufficient to exert its catalytic effect, and to a certain extent, it can avoid the agglomeration caused by the addition of too much catalyst and other solid matter, resulting in poor dispersion of the slurry and affecting the subsequent coating operation.

[0035] Moreover, in order to achieve crack-free or less crack coating in the preparation process, it is necessary to design the catalyst slurry to adopt an organic alcohol system. However, the absorption of alcohols by the anion exchange membrane during direct coating is higher than that of water, and using only alcohol slurry will produce a more severely swollen membrane. Therefore, the present application adds a specific amount of water to address this phenomenon, so that the water-alcohol solvent system is controlled within a certain proportion range, and according to the above-mentioned specific proportion of water-alcohol system, the coating temperature is controlled in the range of 40°C to 100°C with a gradient. In this way, by coordinating the water-alcohol system with a specific proportion and the coating temperature process, it is possible to avoid the severe membrane swelling caused by using only alcohol slurry, and the solvent system can be combined with the specific coating temperature range process parameters during the curing process so that the solvent can be fully and quickly evaporated and dried to achieve crack-free or less crack coating, wherein the reason for controlling the coating temperature within the above range and adopting the above-mentioned gradient heating control is that appropriate heating can avoid swelling and wrinkling of the ion membrane. Because alcohols evaporate quickly, a coating temperature of 40°C can be used for cost considerations, or even without heating. For time efficiency, a coating temperature of 80-100°C can be used to accelerate solvent evaporation. Gradient control of the coating temperature can improve the quality of the resulting catalyst layer.

[0036] In addition, since the coating speed directly affects the thickness and uniformity of the coating, this application also adapts to a specific coating speed process parameter range based on a specific slurry formula design. During the preparation of the membrane electrode, the coating speed is controlled to 0.2-0.5 m / min according to the specific slurry formula. If too high or too low a coating speed is used, the coating quality will be reduced. Moreover, in this application scheme, the coating speed and blade height can be flexibly adjusted to obtain the required catalyst layer thickness.

[0037] In summary, the present application is prepared by a catalyst coating membrane (CCM) method, so that the contact distance between the CCM method catalyst layer and the anion exchange membrane is smaller, the contact gap between the catalyst layer and the anion exchange membrane is eliminated, and the ion conduction resistance is reduced. It can be seen that in the present application scheme, since the cathode catalyst layer and the anode catalyst layer are directly connected to the anion exchange membrane, the impedance of the membrane electrode is small, which is conducive to improving the efficiency of hydrogen production by electrolysis of water. At the same time, the preparation process is simple to operate, and the slurry formula design and preparation process parameters are coordinated so that the swelling of the ion exchange membrane will not be caused during the preparation process, the morphology and structure of the prepared catalyst layer will not be destroyed, and the catalyst layer will not have cracks and fall off, so that the defects of the electrolyzer stack volume expansion and poor sealing will not be caused during the assembly of the electrolyzer stack.

[0038] Based on the above example, the following design is preferred for the membrane electrode slurry formulation and the dimensions of each layer: (1) The thickness of the anion exchange membrane is 20 to 160 μm; The above preparation method provided in this application can be used for anion exchange membranes of all thicknesses, but it is preferred to set the thickness of the anion exchange membrane to 20 to 160 μm. Such anion exchange membrane can effectively conduct anion OH - , and can prevent the anion exchange membrane from rupturing during the process of hydrogen production by water electrolysis.

[0039] When the thickness of the anion exchange membrane is less than 20 μm, for example, when the thickness of the anion exchange membrane is 10 μm, the anion exchange membrane is too thin. During the AEM electrolysis of water to produce hydrogen, a local strong alkaline environment will be formed on the surface of the anion exchange membrane. - Under the action of the anion exchange membrane, it is easy to degrade and cause perforation and rupture, thereby causing the AEM electrolyzer to short-circuit, affecting the operation of electrolysis of water to produce hydrogen and the service life of the AEM electrolyzer. When the thickness of the anion exchange membrane is greater than 160μm, for example, when the thickness of the anion exchange membrane is 170μm, the anion exchange membrane is too thick, resulting in OH - The conduction is slow, which reduces the efficiency of AEM water electrolysis to produce hydrogen.

[0040] (2) The thickness of the cathode catalyst layer and the anode catalyst layer are both 0.1 to 20 μm.

[0041] According to different application scenarios, the thickness of the cathode catalyst layer and the anode catalyst layer can be adaptively adjusted, preferably with a thickness of 0.1 to 20 μm. This design can ensure a good catalytic effect without affecting OH - conduction.

[0042] When the thickness of the catalytic layer is less than 0.1 μm, for example, when the thickness of the cathode catalytic layer is 0.05 μm, the cathode catalytic layer is too thin and the catalytic activity is low, which affects the amount of hydrogen evolution at the cathode and thus affects the efficiency of water electrolysis. When the thickness of the catalytic layer is greater than 20 μm, for example, when the thickness of the cathode catalytic layer is 25 μm, the cathode catalytic layer is too thick, which is not conducive to the OH - conduction, making OH - The conduction from cathode to anode is reduced and slowed down, which ultimately affects the efficiency of AEM water electrolysis.

[0043] (4) The total thickness of the membrane electrode is 0.02 to 0.2 mm.

[0044] The membrane electrode thickness can be adjusted adaptively according to different application scenarios, and the total thickness of the membrane electrode is preferably 0.02 to 0.2 mm. The total thickness of the membrane electrode is within the preferred range above. This ensures the strength of the membrane electrode while reducing the impedance of the membrane electrode, thereby increasing the service life of the electrolyzer and the efficiency of hydrogen production from water electrolysis.

[0045] It should be noted that: The theoretical calculation formula for solid content is: solid content = solid mass / (solid mass + solvent mass); In specific implementation, the raw material ratio of the slurry can be adaptively adjusted within the above-mentioned formula ratio range. According to the different types of catalysts, the alcohol-water ratio and solid content in the slurry are appropriately adjusted so that the total amount is 100% by mass, including but not limited to the specific formula provided in Example 1 below; This application adopts direct coating technology to directly coat the catalyst slurry onto the ion exchange membrane. The specific work flow and working principle of the direct coating technology are existing technologies and will not be repeated here.

[0046] In order to verify the effect of the present invention, the following examples and comparative examples are provided: Example 1 The preparation process of the membrane electrode includes the following steps: Step 1: Cut the anion exchange membrane into the required size and then place it flat on the substrate; wherein the anion exchange membrane is sealed with tape on all sides and vacuum adsorption is maintained to ensure the flatness of the anion exchange membrane; Step 2: Coat the cathode catalyst slurry and the anode catalyst slurry on two opposite sides of the anion exchange membrane, dry and solidify them to form a cathode catalyst layer and an anode catalyst layer, then remove the tape around the anion exchange membrane and package it for storage.

[0047] Among them, the coating speed is 0.35m / min, and the gradient control process of the coating temperature is: the coating temperature is first raised from room temperature to 40°C, and after the coating is completed, it continues to be heated to 60°C and kept at a constant temperature for 15 minutes, and then heated to 80°C, and kept at a constant temperature of 80°C until the formed cathode catalyst layer or the anode catalyst layer is completely dry, and then heating is stopped and naturally cooled.

[0048] The coating temperature specifically refers to the temperature at which the anion exchange membrane is placed on the substrate and heated to a set temperature, which is the coating temperature.

[0049] The cathode catalyst slurry consists of 15% cathode catalyst, 40% deionized water, 35% alcoholic organic solvent, and 10% ionomer solution, calculated by mass. The anode catalyst slurry consists of 20% anode catalyst, 35% deionized water, 40% alcoholic organic solvent, and 5% ionomer solution. The ionomer in the ionomer solution is a poly(biphenylene alkylene) polymer ionomer. The cathode catalyst carrier is a porous carbon nanomaterial, specifically Pt / C. The anode catalyst is specifically RuO2. The alcoholic organic solvent is isopropyl alcohol.

[0050] The membrane electrode produced by the above-mentioned preparation method has a structure comprising an anion exchange membrane having two sides. The first and second sides of the anion exchange membrane are provided with an anode catalyst layer and a cathode catalyst layer, respectively. The anion exchange membrane (AEM membrane) is approximately 95 microns thick, while the anode catalyst layer and cathode catalyst layer are approximately 13.5 microns thick.

[0051] The product obtained in Example 1 was subjected to characterization tests, and the results and analysis are as follows: Figure 1 This is a microscope image of the membrane electrode surface obtained in Example 1. Figure 1 It can be seen that the catalytic layer on the membrane electrode surface has low porosity and is very uniform without cracks.

[0052] Figure 2 This is a scanning electron micrograph of a cross-section of the membrane electrode produced in Example 1 of this application. Position 1 represents the catalyst layer, position 2 represents the AEM membrane, and position 3 represents the interface between the catalyst layer and the AEM membrane. The catalyst layer is approximately 13.5 microns thick, and the AEM membrane is approximately 95 microns thick. Position 3 demonstrates the strong bond between the AEM membrane and the catalyst layer, allowing for flexible control of the thickness of the AEM membrane and catalyst layer during implementation of this application.

[0053] Figure 3 This is a surface scanning electron microscope image of the membrane electrode prepared in Example 1 of the present application. Figure 3 It can be seen that the particles on the membrane electrode surface are evenly distributed.

[0054] Figure 4 The impedance spectrum (EIS) of the membrane electrode prepared in Example 1 of the present application is as follows: Figure 4 It can be seen that when operating at a current density of 1A / cm², the EIS impedance value is measured to be 0.0165Ω.

[0055] Figure 5 The polarization curve of the membrane electrode prepared in Example 1 of the present application is as follows: Figure 5 It can be seen that at a constant voltage of 1.8V, the current density reaches 2.4A / cm 2 .

[0056] Figure 6 The membrane electrode product prepared in Example 1 of this application is Figure 6 It can be seen that the surface of the product is smooth, without peeling or swelling.

[0057] above Figure 1-6 The results show that the membrane electrode prepared in Example 1 of the present application has the advantages of low impedance, high catalytic activity, low swelling rate, and firm bonding between the catalytic layer and the anion exchange membrane.

[0058] It should be noted that: In this article, “~” is used to indicate a numerical range, and the range indicated by this expression includes two endpoint values.

[0059] The specific parameters or some commonly used reagents or raw materials in the above embodiments are specific embodiments or preferred embodiments of the present application, and are not intended to limit the present application. Those skilled in the art may make adaptive adjustments within the scope of the present application.

[0060] In addition, unless otherwise specified, the raw materials used may also be conventional commercial products in the art, or prepared by conventional methods in the art; that is, the reagents and instruments used in this embodiment are not marked with information such as the manufacturer, and are all conventional products that can be purchased on the market.

[0061] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit them. Although the present application has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or make equivalent replacements for some or all of the technical features therein. These modifications or replacements do not deviate the essence of the corresponding technical solutions from the scope of the technical solutions of the embodiments of the present application.

Claims

1. A membrane electrode for producing hydrogen by electrolysis of water using an anion exchange membrane, characterized in that: comprising an anion exchange membrane having two sides; The first side of the anion exchange membrane is provided with a cathode catalyst layer; and / or the second side of the anion exchange membrane is provided with an anode catalyst layer; The cathode catalyst layer is a solid catalyst layer formed by coating the cathode catalyst slurry on the first side of the anion exchange membrane and curing; the anode catalyst layer is a solid catalyst layer formed by coating the anode catalyst slurry on the second side of the anion exchange membrane and curing; The components of the cathode catalyst slurry include, by mass fraction: 15% to 20% cathode catalyst, 35% to 40% water, 35% to 40% alcohol organic solvent, and 5% to 10% ionomer solution; Calculated by mass fraction, the components of the anode catalyst slurry include: 15% to 20% of anode catalyst, 35% to 40% of water, 35% to 40% of alcohol organic solvent, and 5% to 10% of ionomer solution.

2. The membrane electrode for producing hydrogen by electrolysis of water using an anion exchange membrane according to claim 1, characterized in that: The cathode catalyst slurry is composed of cathode catalyst, water, alcohol organic solvent, and ionomer solution, and the cathode catalyst slurry is obtained by stirring and mixing the cathode catalyst, water, alcohol organic solvent, and ionomer solution for 3 to 5 hours; The components of the anode catalyst slurry are composed of an anode catalyst, water, an alcohol organic solvent, and an ionomer solution. The anode catalyst slurry is obtained by stirring and mixing the anode catalyst, water, an alcohol organic solvent, and the ionomer solution for 3 to 5 hours.

3. The membrane electrode for producing hydrogen by electrolysis of water using an anion exchange membrane according to claim 1, characterized in that: During the coating of the cathode catalyst slurry and the anode catalyst slurry, the coating is performed by gradient controlling the coating temperature at 40° C. to 100° C., and the coating speed is 0.2 to 0.5 m / min; The process of gradient controlling the coating temperature of 40°C to 100°C is as follows: the coating temperature is first raised from room temperature to 40-50°C, and after coating is completed, the temperature is continued to be raised to 60°C and maintained at a constant temperature for 15 minutes, and then the temperature is raised to 80-100°C, and the constant temperature of 80-100°C is maintained until the formed cathode catalyst layer or the anode catalyst layer is completely dry, and the heating is stopped.

4. The membrane electrode for producing hydrogen by electrolysis of water using an anion exchange membrane according to claim 1, characterized in that: The ionomer in the ionomer solution is a polybiphenyl alkylene polymer ionomer, so that the cathode catalyst layer or the anode catalyst layer forms a firm electrode structure; The carrier of the cathode catalyst is a porous carbon nanomaterial; and the alcohol organic solvent is isopropanol.

5. The membrane electrode for producing hydrogen by electrolysis of water using an anion exchange membrane according to claim 1, characterized in that: The thickness of the anion exchange membrane is 20 to 160 μm.

6. The membrane electrode for producing hydrogen by electrolysis of water using an anion exchange membrane according to claim 1, characterized in that: The thickness of the cathode catalyst layer and the anode catalyst layer are both 0.1 to 20 μm.

7. The membrane electrode for producing hydrogen by electrolysis of water using an anion exchange membrane according to claim 1, characterized in that: The total thickness of the membrane electrode is 0.02-0.2 mm.

8. A method for preparing a membrane electrode for producing hydrogen by electrolysis of water using an anion exchange membrane, characterized in that: The following steps are involved: Cutting the anion exchange membrane into required specifications and sizes; Coating cathode catalyst slurry and anode catalyst slurry on two opposite sides of the anion exchange membrane, respectively, and drying and curing them to form a cathode catalyst layer and an anode catalyst layer on the two sides of the anion exchange membrane, respectively; Wherein, the components of the cathode catalyst slurry include, by mass fraction: 15% to 20% cathode catalyst, 35% to 40% water, 35% to 40% alcohol organic solvent, and 5% to 10% ionomer solution; Calculated by mass fraction, the components of the anode catalyst slurry include: 15% to 20% of anode catalyst, 35% to 40% of water, 35% to 40% of alcohol organic solvent, and 5% to 10% of ionomer solution.

9. The method for preparing a membrane electrode for producing hydrogen by electrolysis of water using an anion exchange membrane according to claim 8, characterized in that: During the coating of the cathode catalyst slurry and the anode catalyst slurry, the coating is performed by gradient controlling the coating temperature of 40° C. to 100° C., and the coating speed is 0.2 to 0.5 m / min; Among them, the process of gradient controlling the coating temperature of 40℃~100℃ is: the coating temperature is first increased from room temperature to 40~50℃, and after the coating is completed, the temperature is continued to be increased to 60℃ and maintained at a constant temperature for 15 minutes, and then the temperature is increased to 80~100℃, and the constant temperature of 80~100℃ is maintained until the formed cathode catalyst layer or the anode catalyst layer is completely dry, and the heating is stopped.

10. The method for preparing a membrane electrode for producing hydrogen by electrolysis of water using an anion exchange membrane according to claim 8, characterized in that: The following steps are involved: Cutting the anion exchange membrane into the required size, and then placing the anion exchange membrane flat on the substrate; wherein the anion exchange membrane is sealed with tape around the periphery, and vacuum adsorption is maintained to ensure that the anion exchange membrane is flat; Cathode catalyst slurry and anode catalyst slurry are coated on two opposite sides of the anion exchange membrane respectively, dried and solidified to form a cathode catalyst layer and an anode catalyst layer, and then the tape around the anion exchange membrane is removed and the membrane is packaged for storage.

Citation Information

Patent Citations

  • Membrane electrode for water electrolysis, preparation method of membrane electrode and water electrolysis tank

    CN115786950A

  • Anode for anion exchange membrane water electrolysis, preparation method of anode and water electrolysis tank

    CN115874223A

  • Preparation of patterned cathode acid-base catalyst layer membrane electrode

    CN116404217A

  • Membrane electrode for AEM water electrolysis hydrogen production and preparation method thereof

    CN117286526A

  • AEM anode slurry and preparation method of membrane electrode of AEM anode slurry

    CN118207566A

Cited By

  • Cationic COF-doped AEM electrode and preparation method and application thereof

    CN121951586A

  • AEM electrolytic cell assembly process and membrane electrode preparation method

    CN122013217A